Foundations in Digital Marketing - Grayson, Rochelle (Open textbook library., 2024)
Foundations in Digital Marketing is a textbook intended to introduce marketing students to the world of digital marketing. The book covers fundamental frameworks, practical applications, and online tools that can all be applied to build and execute a cohesive and engaging digital marketing strategy. The book covers the fundamental aspects of digital marketing, including areas such as: visual storytelling, design principles and frameworks, search engine optimization and marketing, website and landing page optimization, content marketing, content creation tools and technologies, paid advertising, social media marketing, mobile marketing, email marketing, attribution, conversion rate optimization, data and marketing analytics, and the future of digital marketing. The book also features chapter learning objectives, videos, summaries, interactive learning activities, and discussion points, as well as recommended industry certifications and online resources to augment the textbook.